A high-response ethanol gas sensor based on one-dimensional TiO2/V2O5 branched nanoheterostructures. (19th September 2016) - Wang, Yuan; Zhou, Yun; Meng, Chuanmin; Gao, Zhao; Cao, Xiuxia; Li, Xuhai; Xu, Liang; Zhu, Wenjun; Peng, Xusheng; Zhang, Botao; Lin, Yifeng; Liu, Lixin
Abstract: Hierarchical nanostructures with much increased surface-to-volume ratio have been of significant interest for prototypical gas sensors. Herein we report a novel resistive gas sensor based on TiO2 /V2 O5 branched nanoheterostructures fabricated by a facile one-step synthetic process, in which well-matched energy levels induced by the formation of effective heterojunctions between TiO2 and V2 O5, a large Brunauer–Emmett–Teller surface area and complete electron depletion for the V2 O5 nanobranches induced by the branched-nanofiber structures are all beneficial to the change of resistance upon ethanol exposure. As a result, the ethanol sensing performance of this device shows a lower operating temperature, faster response/recovery behavior, better selectivity and about seven times higher sensitivity compared with pure TiO2 nanofibers. This study not only confirms the gas sensing mechanism for performing enhancement of branched nanoheterostructures, but also proposes a rational approach to the design of nanostructure-based chemical sensors with desirable performance.